2021
DOI: 10.1002/hed.26936
|View full text |Cite
|
Sign up to set email alerts
|

Functional swallowing outcomes related to radiation exposure to dysphagia and aspiration‐related structures in patients with head and neck cancer undergoing definitive and postoperative intensity‐modulated radiotherapy

Abstract: Background The relationship between swallowing outcomes and radiotherapy dose to dysphagia and aspiration‐related structures (DARS) may be different following definitive versus postoperative radiotherapy (PORT) for mucosal head and neck cancer (HNC) and has not been well‐studied. Method Patient‐ and clinician‐reported swallowing measures were prospectively collected at six time points from baseline to 24 months postradiotherapy HNC. Radiotherapy plans were retrospectively analyzed to assess dose delivered to D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…The most debilitating adverse effects of head and neck radiotherapy are dysphagia and aspiration. There are many studies in literature evaluating the role of Do‐IMRT in head and neck cancer patients 18,24–34 . Most of these studies either had only pharyngeal carcinoma or the number of oral cavity carcinoma patients were very small.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most debilitating adverse effects of head and neck radiotherapy are dysphagia and aspiration. There are many studies in literature evaluating the role of Do‐IMRT in head and neck cancer patients 18,24–34 . Most of these studies either had only pharyngeal carcinoma or the number of oral cavity carcinoma patients were very small.…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies in literature evaluating the role of Do-IMRT in head and neck cancer patients. 18,[24][25][26][27][28][29][30][31][32][33][34] Most of these studies either had only pharyngeal carcinoma or the number of oral cavity carcinoma patients were very small. Charters et al had shown that there is a dose/outcome relationship for the dose of radiation received by DARS and dysphagia which may vary between definitive and post-op RT.…”
Section: Dosimetric and Clinical Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…Avoiding GI may be crucial in postradiation PGS in whom there is commonly an already impaired swallowing mechanism and therefore are more prone to aspirations. [28][29] Comparably, in post-intubation PGS patients there is often a pulmonary comorbidity and aspirations might result in devastating outcomes. The previously described techniques for correcting PGS generally have a high rate of GI symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The key rationale behind the DISCO protocol is to avoid the tradeoff between airway opening and GI symptoms. Avoiding GI may be crucial in post‐radiation PGS in whom there is commonly an already impaired swallowing mechanism and therefore are more prone to aspirations 28–29 . Comparably, in post‐intubation PGS patients there is often a pulmonary comorbidity and aspirations might result in devastating outcomes.…”
Section: Discussionmentioning
confidence: 99%